Cannabis use and car crashes: a review - Preuss, Ulrich W.; Huestis, Marilyn A.; Schneider, Miriam; Hermann, Derik; Lutz, Beat; Hasan, Alkomiet; Kambeitz, Joseph; Wong, Jessica W. M.; Hoch, Eva (Frontiers in psychiatry, 2021)
In this review, state-of-the-art evidence on the relationship between cannabis use, traffic crash risks, and driving safety were analyzed. Systematic reviews, meta-analyses, and other relevant papers published within the last decade were systematically searched and synthesized. Findings show that meta-analyses and culpability studies consistently indicate a slightly but significantly increased risk of crashes after acute cannabis use. These risks vary across included study type, crash severity, and method of substance application and measurement. Some studies show a significant correlation between high THC blood concentrations and car crash risk. Most studies do not support this relationship at lower THC concentrations. However, no scientifically supported clear cut-off concentration can be derived from these results. Further research is needed to determine dose-response effects on driving skills combined with measures of neuropsychological functioning related to driving skills and crash risk.